Steering Committee Assam Economic Development - Planning Commission (Planning Commission, 1985)
Our entire thinking have been influenced by one major factor: a fairly well informed and fervent demand for development from the people at large — students, political parties, women’s groups, voluntary organisations, economists, ministers, administrators, entrepreneurs - with whom we had the privilege of interacting. This magnitude of popular awareness and interest in development is a rare social force. Constructively used, it can be the most precious capital for the development of Assam.
Planning Commission Government of India
Planning Commission Government of India